The mediating role of locus of control: Financial knowledge and financial attitude on financial management behavior - Hefri, Besse Nur Fatimah (Journal of Management and Business Insight, 2023)
Purpose-Currently, individual behavior in managing finances, especially in the younger generation, needs attention. The ease of financial access can provide both positive and negative aspects. This study aimed to ascertain how financial knowledge and attitudes through locus of control can influence financial management behavior. Design/Methodology/Approach-Modeling structural equations using Smart PLS 4.0 are the data processing techniques used in this study. This study examines the impact of the indicators of each of these variables on the objects of students of the Faculty of Economics and Business in Yogyakarta, Indonesia. By distributing questionnaires, the researchers were able to collect data from up to 98 respondents. Findings-The study's findings suggest that although financial attitudes have a direct impact on financial behavior management, financial knowledge has no direct impact on financial behavior management behavior. Financial attitudes and knowledge have been demonstrated to directly affect locus of control. It has also been demonstrated that locus of control directly affects money management behavior. Furthermore, it has been demonstrated that locus of control mediates the relationship between financial knowledge and financial management behavior, but not the relationship between financial attitudes and financial management conduct. Research limitations/implications-The findings of this research are expected to be a reference and basis for knowledge, especially for the younger generation, who are expected to understand that to foster good financial management behavior, there are many things that must be considered. This study shows that financial knowledge, financial attitudes, and locus of control are elements that can influence financial management behavior. Originality/value-There is still very little research on financial management behavior in the younger generation, especially among students of the Faculty of Economics and Business in Yogyakarta, Indonesia. This study revealed factors that allegedly had an impact on the financial management behavior of students of the Faculty of Economics and Business in Yogyakarta, Indonesia.